In vitro Assessment of Antibacterial Activity and Potential Genotoxic Effect of Fruit Extracts of Capparis spinosa L. Plant - Adwan, Ghaleb (Jordan Journal of Pharmaceutical Sciences, 2023)
This research was carried out to assess the minimum inhibitory concentration (MIC) and the genotoxic potential of ethanolic and aqueous (cold and hot) fruit extracts of Capparis spinosa L. (C. spinosa) plant against different types of bacterial strains. The antimicrobial effect of these extracts against the tested bacteria was investigated using broth microdilution method. The potential genotoxic effect was evaluated by ERIC-PCR technique. Results of the current study revealed that the MIC values of ethanolic fruit extract against the tested bacterial had a range of 12.5 mg/ml to 25 mg/ml. However, aqueous fruit extracts had an MIC with a range of 50 mg/ml to 100 mg/mL. The potential genotoxic activity of cold aqueous extract was determined according to the changes in ERIC-PCR profile of E. coli strain treated with extract in comparison to that untreated (negative control). Results of this study suggest the genotoxic effect of aqueous fruit extract on E. coli. Further research is required to assess and identify the biological molecules and their mechanisms in the context of the genotoxicity. In vivo genotoxicity assessment or with the presence of liver extract is recommended to evaluate the safety of using fruits for therapeutic purposes and a valuable nutrient source.